Praktik All You Can Eat Dalam Tinjauan Hukum Islam - Muhammad Hafiz Fajar Hidayah; Maulana al-Ghifari Harahap; Mutiara Liza; Rini Fadila Tunnisa Harahap; Ayu Hijrani Salamah (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The practice of “All You Can Eat” (AYCE) is a food serving model where customers pay one fixed price to enjoy various types of all-you-can-eat dishes within a certain time limit. This concept has become a global trend and is widely implemented in Indonesia, especially in Japanese and Korean themed restaurants. As a modern form of muamalah, AYCE raises questions in the perspective of Islamic law because it involves aspects of economic transactions that must fulfill the pillars and conditions of buying and selling according to Islam. This study examines the mechanism of AYCE, starting from the payment system, time policy, and additional rules such as fines for uneaten food. In addition, it discusses the application of the pillars and conditions of buying and selling in Islam, which include clarity of goods, valid contracts, and voluntary consent of the parties involved. The main focus is on the potential element of uncertainty (gharar) in AYCE practices, especially regarding the different portions of food consumed by customers, which forms the basis of the Islamic legal analysis of this concept. This research aims to provide a comprehensive view of the relationship between the AYCE concept in the light of Islamic law.